Para-tert-butylcumene synthesis - E. M. Yarkina; E. A. Kurganova; A. S. Frolov; G. N. Koshel; T. N. Nesterova; V. A. Shakun; S. A. Spiridonov (Тонкие химические технологии, 2021)
Objectives. This study describes a new approach to obtain para-tert-butylcumene by alkylation of cumene with isobutylene in the presence of catalysts, such as Amberlyst 36 Dry, KU-2-8, aluminum chloride, and tert-butyl alcohol and concentrated sulfuric acid.Methods. To determine the qualitative and quantitative composition of the compounds and reaction masses, the following analysis methods were used: gas–liquid chromatography (on the Kristall 2000M hardware-software complex), chromatomass spectrometry on an Agilent 6850 instrument equipped with an Agilent 19091S-433E capillary column (30 m × 250 μm × 0.25 μm), and nuclear magnetic resonance spectroscopy (on a Bruker DRX 400 instrument with an operating frequency of 400 MHz).Results. A significant quantity of meta-tert-butylcumene was obtained by the alkylation of cumene with isobutylene using several catalysts, along with para-tert-butylcumene. This study also showed that the use of the catalysts Amberlyst 36 Dry and KU-2-8 during alkylation in a closed system (autoclave) led to the formation of isobutylene oligomers, often in quantity greater than the target reaction product. Simultaneously, the alkylation of cumene with tert-butyl alcohol in the presence of concentrated sulfuric acid enabled the obtainment of only one isomer, para-tertbutylcumene, which is essential for the further production of high-purity para-tert-butyl phenol.Conclusions. Sulfuric acid alkylation of cumene with tert-butyl alcohol enabled the obtainment of an individual para-isomer of tert-butylcumene with a yield of 87–89% for the loaded tert-butyl-alcohol with a cumene conversion of ~30%.